Retrospective Study of Selective Submandibular Neck Dissection versus Radical Neck Dissection for N0 or N1 Necks in Level I Patients with Oral Squamous Cell Carcinoma. (28th May 2012) - Yanai, Yuta; Sugiura, Tsuyoshi; Imajyo, Ikumi; Yoshihama, Naoya; Akimoto, Naonari; Kobayashi, Yosuke; Hayashi, Kohei; Fujinaga, Takahiro; Shirasuna, Kanemitsu; Takenoshita, Yasuharu; Mori, Yoshihide
Abstract : Objective . To evaluate the efficacy of selective submandibular neck dissection (SMND) in patients with oral squamous cell carcinoma (OSCC) with or without nodal metastasis. Patients . From a total of 384 patients with untreated OSCC who underwent radical excision, we identified 229 with clinically N0 necks and 68 with clinically N1 necks in level I. Main Outcome Measures . The Kaplan-Meier 5-year regional control and 5-year disease specific survival (DSS) were compared for SMND, radical neck dissection (RND), and modified radical neck dissection (MRND). Results . In clinically node-negative necks, the regional control rates were 85.2% with SMND and 83.3% with MRND (P = 0.89 ), and 5-year DSS rates were 86.5% and 87.0%, respectively, (P = 0.94 ). In clinically N1 necks, the regional control rates were 81.3% with SMND and 83.0% with RND (P = 0.72 ), and the DSS rates were 81.3% and 80.0%, respectively, (P = 0.94 ). Type of neck dissection was not significantly associated with regional control or DSS on either univariate or multivariate analysis using Cox's proportional hazard model. Conclusions . SMND can be effectively applied in elective and therapeutic management to patients with OSCC that are clinically assessed as N0 or N1 to level I of the neck.